Pendidikan Karakter dalam Tradisi "Larung Sesaji" - Victor Novianto; Ali Mustofa; Nugraeni Putrie Windarti (Proceedings Series on Social Sciences & Humanities, 2023)
Tri Hita Karana which is described in the process of offering offerings. Through offering offerings, the younger generation is taught to live in balance and in harmony with their surroundings and to be grateful to God. Meanwhile, the concept of Tri Kaya Parisudha prohibits the formation of character through three aspects, namely thoughts, words and actions that are sacred. In the tradition of offering offerings, the younger generation learns to control their thoughts, speak good words, and perform useful deeds. The method used in this study is to use qualitative methods. Data collection techniques used are participatory observation techniques, interviews, and documentation studies. Meanwhile, the data collection tools are observation guides, interview guides, and documentation. Larung sesaji is an important moment in an effort to instill positive values and good character in the younger generation. Through this tradition, they are taught to live in balance with nature and interact with fellow human beings with sacred thoughts, words and deeds.